HUBUNGAN LAJU INFILTRASI TERHADAP PERMEABILITAS TANAH DAN MUKA AIRTANAH DI DAERAH DESA TAJUR KECAMATAN CITEUREUP: THE RELATIONSHIP OF INFILTRATION RATE TO SOIL PERMEABILITY AND GROUNDWATER LEVEL IN THE TAJUR AREA, CITEUREUP DISTRICT - Anwar, Saepul; Amri, Muhammad Adimas (Journal of Geoscience Engineering and Energy, 2024)
Infiltration is an important process in a hydrological system and acts as a medium for air infiltration into the soil. The process of infiltration in soil can be influenced by several factors, namely, rainfall, vegetation, land slope, land use, and soil moisture. Apart from this, other factors such as groundwater level and soil permeability also have an influence on the infiltration process, both of which are related to each other in terms of the rate of infiltration or air infiltration into the soil. If the infiltration process is disrupted, it results in the pooling of air on the ground surface, which affects the hydrological system. It is necessary to know how factors such as groundwater levels and soil permeability influence the infiltration rate. Based on this, the aim of this research is to determine the relationship. between infiltration rate, groundwater level, and soil permeability and their influence. The research method was carried out by taking data from direct groundwater level measurements and infiltration rate measurements, as well as samples for soil permeability analysis. Then an interpretation of the data obtained is carried out and presented in a map of the infiltration zone and soil permeability zone. The research area in Tajur Village has 2 infiltration zones, namely the slow-medium zone and the medium zone with medium and rather fast soil permeability and low-medium groundwater depth.